POCKET BOOK DIGITAL BERBASIS ETNOMATEMATIKA SEBAGAI BAHAN AJAR SEKOLAH MENENGAH PERTAMA - Ika Herawati; Fredi Ganda Putra; Rubhan Masykur; Chairul Anwar (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2020)
The purpose of this research is to know the development, response and effectiveness of learning using a digital pocket book characterized by Ethnomatematics for junior High School. Research and Development methods. Data Analysis techniques Research on the development of digital pocket books using 2 qualitative and quantitative analytical techniques. Data collection techniques are obtained via polls, interviews, documentation, and tests. The research Model with ADDIE is analysis, design, development, implementation, and Evaluation (evaluation), and assessment. Research conducted at SMPN 7 Metro. The results of this study with students ' responses from the use of digital pocket books characterized by ethnomatematics in small scale tests were obtained on average of 3.49 with